Ecologia reprodutiva de espécies de Psychotria L. (Rubiaceae) em fragmentos de floresta estacional semidecidual - Rodrigues, Ebenézer Barbosa (2013)
Distyly is a floral polymorphism governed by genetic and ecological elements. Typical distylous species present two floral morphs that occur in equal proportion on its populations, the pin morph with the stigma positioned above the anthers, and the thrum morph, with the stigma below the anthers height. Distylous flowers also exhibit reciprocal positioning of the anthers and stigma height in the flower. And there is the presence of an incompatibility system that prevents fertilization by selfing and intramorph pollinations. The aim of this study was to investigate the distylous characteristics of Psychotria species (Rubiaceae) in the Triangulo Mineiro, and understand whether the stigmatic pollen load, the population density and the spatial distribution of floral morphs, could explain the occurrence of distyly variations found in the studied species, in areas with different levels of anthropogenic disturbance. We studied 24 populations of 9 Rubiaceae species: Psychotria capitata Ruiz & Pav., P. carthagenensis Jacq., P. deflexa DC., P. goyazensis Müll. Arg., P. hoffmannseggiana (Willd. ex Roem. & Schult.) Müll. Arg., P. poeppigiana Müll. Arg., P. prunifolia (Kunth) Steryerm. and P. trichophoroides Mull. Arg. The presence of incompatibility and isoplety were found in the typical distylous species. Otherwise, monomorphic species presented self-compatibility. Atypical distylous populations showed anisoplety, the deviation in the ratio of 1:1 between the floral morphs and we also registered pin monomorphism in some species. The reciprocal herkogamy between the morphs did not perfectly occur, but high values of reciprocity were evidenced in all populations. The intensity of anthropogenic disturbance showed no relationship with the presence or absence of isoplety, reciprocal herkogamy and incompatibility in the species. The manifestations of distyly and its variations in species of the study were also confirmed in observations made in different Brazilian herbariums. Populations had low frequencies of stigmatic pollen load, and in some of them, pollen grains were absent on its flowers. Most populations presents aggregated distribution pattern. Different spatial patterns were found among the floral morphs of anisoplety populations, indicating a spatial segregation of the floral morphs within the populations. The majority of the populations have low densities. We found a weak but significant relationship, between the increase in intensity of anthropogenic disturbance and the reduction in the density in the Psychotria populations of the study. Monomorphic populations of P. prunifolia had higher population density compared to typical distylous populations of P. hoffmannseggiana. Distylous anomalies may be related to the population size and are governed by ecological and evolutionary factors. The presence of monomorphism and self-compatibility can be an advantage in disturbed areas, whose human impacts may present limitations to the reproduction in these species compared to distylous populations that require a regular intermorph pollen flow for their breeding. The low frequency of stigmatic pollen load may be an evidence of pollen limitation in the analyzed populations. Different spatial patterns among the floral morphs appears to be influenced by the anisoplety, and result in greater distances to occur intermorph pollen flow, and this may represent risks for the reproduction and the fitness of these species. It was not possible to determine whether the anomalies found in distyly, the possible pollen limitation, and the reduced population size of the analyzed Psychotria species, are responses to recent or historical ecological disturbances in the study areas. Moreover, it is necessary to consider the influences of the founder effects, the stochastic events and the different selective pressures that these species and the ecosystems that they occur were subjected throughout their life stories, in order to elucidate the ecological and evolutionary paths that have shaped the evolution of distyly and their variations in the genus Psychotria.